EFEKTIVITAS MEDIA KARTU CERITA DALAM MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS IV SEKOLAH DASAR - Anugrah Agung; Lusi Lastriani; Salamah .; Masrifa Hidayani; Khermarina . (LPPM Universitas PGRI Silampari Lubuklinggau, 2026)
This study aims to determine the effectiveness of story card media in improving the speaking skills of fourth-grade elementary school students. This research employed Classroom Action Research (CAR) involving 32 students at MIS Hidayatul Hasaniyyah in the second semester of the 2026 academic year. The study was conducted in two cycles consisting of planning, action, observation, and reflection stages. Data were collected through speaking performance tests and observation sheets, then analyzed using descriptive quantitative methods by calculating mean scores and learning completeness percentages. The results showed a significant improvement in students’ speaking skills. The average score increased from 45.62 in the pre-cycle to 63.72 in Cycle I, and further improved to 82.78 in Cycle II. In terms of learning completeness, only 9.38% of students achieved the minimum mastery criterion (KKM = 70) in the pre-cycle, which increased to 46.88% in Cycle I and reached 87.50% in Cycle II. In Cycle I, picture-based story cards were used to stimulate students’ ideas, while in Cycle II, text-based story cards with contextual themes were applied to enhance students’ ability to organize and express ideas more systematically. These findings indicate that story card media is effective in improving students’ speaking skills, both in terms of performance and learning completeness. The gradual use of visual and textual media also contributes to increasing students’ confidence and participation in learning.